Open Framework Middleware for Intelligent WSN Topology Adaption in Smart Buildings - BRENNAN, ROB; O'SULLIVAN, DECLAN (IEEE, 2009)
Modern smart buildings utilize sensor networks for facilities management applications such as energy monitoring. However as buildings become progressively more embedded with sensor networks, the challenge of managing and maintaining the sensor networks themselves becomes ever more significant. As a cost-sensitive activity, facilities management deployments are less likely to deploy node redundancy and specialized technical staff to maintain these networks. Hence there are strong requirements for the network to efficiently self-diagnose, self-heal and integrate with standard buildings management systems. This paper introduces a solution for WSN management in smart buildings that addresses these issues. It is based on the deployment of the open framework middleware for sensor networks coupled with a structured knowledge and rule-based fault analysis engine to perform network event correlation and root cause analysis. The system also explicitly interfaces with a building management system (BMS) or the scheduling of network maintenance activities such as sensor battery replacement.
International Conference on Ultra Modern Telecommunications & Workshops, 2009. ICUMT '09.
PUBLISHED
St Pertersburg, Russia
Keywords: BMS; Topology Management; OFM; Rules-based Reasoner; Ontology; Intelligent Content & Communications; Telecommunications